Prinsip Sistemik Lembaga Perdamaian PKPU Untuk Mencapai Nilai Keadilan - Suci, Ivida Dewi Amrih; Shubhan, M. Hadi; Poesoko, Herowati; R. Murjiyanto; Zahir, Mohd Zamre Mohd; Sudiyana (Media Iuris, 2024)
Systemic principles serve as the basic basis for thought and action processes, representing interconnected elements that contribute to the formation of a comprehensive whole. Bankruptcy law is a special and special law, regulated in Articles 222 to 294 of the Bankruptcy Law and PPU, PKPU is a legal peace institution whose operational elements include deciding judges, administrators, supervisory judges, debtors, creditors, and additional elements in the PKPU institution that are guarantors if provided. Systemically, these elements are interrelated both within their own elements and with theoretical elements, namely the Ideal elements (about meaning) and the actual elements. According to Article 287 of the Bankruptcy Law and PKPU Jo Article 282 of the Bankruptcy Law and PKPU, PKPU has a final and binding decision, but it is limited, and its decision is only related to the minutes of the meeting. The verdict still has legal consequences if violated. The author's motivation is to analyze systemic principles in the legal framework of PKPU peace institutions with the aim of upholding the principle of justice. The analysis methodology used is the legal system theory developed by Kees Schuit, focusing on the Ideal, Operational, and Actual elements. In addition, it incorporates three basic principles outlined by Gustav Radbruch – Certainty, Benefit, and Justice. The results of this study contribute prescriptive value to the field of law, especially in bankruptcy law.